RGS1 silencing inhibits the inflammatory response and angiogenesis in rheumatoid arthritis rats through the inactivation of Toll‐like receptor signaling pathway. Issue 11 (22nd April 2019) - Hu, Xumin; Tang, Jianhua; Zeng, Gang; Hu, Xuyun; Bao, Peng; Wu, Jionglin; Liang, Yuwei; Deng, Weixi; Tang, Yong
Abstract: Emerging evidence shows that rheumatoid arthritis (RA) progression can be induced by the activation of Toll‐like receptor (TLR) signaling pathway. Regulator of G‐protein signaling 1 (RGS1) is observed to be a candidate biomarker for arthritis. Accordingly, the present study aims to determine the potential effects of RGS1 mediating TLR on RA. A rat model of collagen‐induced arthritis (CIA) was established to mimic the features of RA by injection of bovine type II collagen. The rats with CIA were treated with short hairpin RNA (shRNA) against RGS1 or TLR pathway activator Poly I:C to elucidate the role of RGS1 in RA progression. The inflammatory factors were measured, and the thoracic gland and spleen indexes as well as the vascular density were determined. The expression levels of RGS1, TLR3, vascular endothelial growth factor (VEGF), metalloproteinase‐2 (MMP‐2), MMP‐9, and interleukin 1 receptor‐associated kinase‐4 (IRAK4) were determined. RGS1 was robustly increased in RA. The TLR signaling pathway was suppressed by RGS1 silencing. shRNA‐mediated depletion of RGS1 was shown to significantly enhance thoracic gland index and inhibit the serum levels of TNF‐α, IL‐1β, and IL‐17, spleen index, vascular density, and the expression levels of TLR3, VEGF, MMP‐2, MMP‐9, and IRAK4. However, when the rats with CIA were treated with Poly I:C, the trend of effects was opposite. These findings highlight that functional suppression of RGS1 inhibits the inflammatory response and angiogenesis by inactivating the TLR signaling pathway in rats with CIA, thereby providing a novel therapeutic target for RA treatment. Abstract : These findings highlight that functional suppression of RGS1 inhibits the inflammatory response and angiogenesis by inactivating the TLR signaling pathway in rats with CIA, thereby providing a novel therapeutic target for RA treatment.